(untitled) (Bangladesh Journal of Agriculture, 2022)
Aflatoxin (AF), a secondary metabolite of Aspergillus species, is carcinogenic and mutagenic for chicken. Chickens are highly sensitive to the adverse effect of AF and it is causing economic loss in poultry industry. The aim of the current study was to evaluate the efficacy of turmeric powder (TP) and garlic powder (GP) on broiler receiving diet containing exogenous AF. Randomly selected 14 days old cobb-500 broiler chicks (N=84) were equally divided into four treatments. Four isonitrogenous and isocaloric experimental diets were prepared viz; diet-A: 1.5 mg of AF; Diet-B: 1.5 mg of AF and 1g of TP; Diet-C: 1.5 mg of AF and 1 g of GP contained per kg feed and control diet had no AF, TP and GP. Each dietary treatment had 3 replications (having 7 birds in each) and respective feed was offered to the broilers according to the entire duration (35 days) of experiment. All experimental broilers were reared following same management practices. At 36 days of age all experimental broiler were slaughtered for examining the necroscopic changes in internal organs such as liver, kidney and spleen to estimate AF residues. Growth of the broiler chicken was monitored and feed conversion ratio (FCR) was calculated. The study demonstrated significant (P<0.01) effect of turmeric and garlic powder on final body weight of birds and so also the FCR. Liver and kidney weight use showed significantly (P<0.01) the highest in diet-A, followed by diet-B, diet-C and the control diet, respectively but, spleen weight did not differ significantly (p>0.05) with the treatments. The residue of AF in different internal organs was also significantly (P<0.05) different between the treatments; being higher in diet-A as compared to the rest of the dietary treatment groups. Evidently, the present study substantiated the potentiality of TP in broiler chicken to overcome the adverse effect of AF, a common mycotoxin. Bangladesh J. Agri. 2019-2021, 44-46: 89-95